Solar Water Splitting with a Hydrogenase Integrated in Photoelectrochemical Tandem Cells. (17th July 2018) - Nam, Dong Heon; Zhang, Jenny Z.; Andrei, Virgil; Kornienko, Nikolay; Heidary, Nina; Wagner, Andreas; Nakanishi, Kenichi; Sokol, Katarzyna P.; Slater, Barnaby; Zebger, Ingo; Hofmann, Stephan; Fontecilla‐Camps, Juan C.; et al.
Abstract: Hydrogenases (H2 ases) are benchmark electrocatalysts for H2 production, both in biology and (photo)catalysis in vitro. We report the tailoring of a p‐type Si photocathode for optimal loading and wiring of H2 ase through the introduction of a hierarchical inverse opal (IO) TiO2 interlayer. This proton‐reducing Si|IO‐TiO2 |H2 ase photocathode is capable of driving overall water splitting in combination with a photoanode. We demonstrate unassisted (bias‐free) water splitting by wiring Si|IO‐TiO2 |H2 ase to a modified BiVO4 photoanode in a photoelectrochemical (PEC) cell during several hours of irradiation. Connecting the Si|IO‐TiO2 |H2 ase to a photosystem II (PSII) photoanode provides proof of concept for an engineered Z‐scheme that replaces the non‐complementary, natural light absorber photosystem I with a complementary abiotic silicon photocathode.